The Role of Legal Aid and Consultation Agencies by Faculty of Law University of Muhammadiyah Sukabumi in Preventing Domestic Violence - Kusumah, Haidan Angga Kusumah; Ginalita Dwi Putri, R Eriska; Rachmawati, Ike (Ius Poenale, 2023)
This research was conducted to examine the suboptimal governmental, social, and law enforcement efforts in reducing domestic violence, particularly the insufficient legal support provided by legal aid institutions for domestic violence cases in Sukabumi Regency. The research aimed to develop strategic intervention models for the Legal Assistance and Consultation Institute (LBKH) at the Faculty of Law, University of Muhammadiyah Sukabumi, to address domestic violence. Utilizing a descriptive-analytic method, the research analyzed existing data through juridical foundations and employed both qualitative and quantitative approaches to investigate and conceptualize coordination between LBKH and local village governments. The findings indicated that strategic cooperation between LBKH and local authorities could significantly reduce domestic violence in Sukabumi Regency by integrating efforts across social institutions, law enforcement, and legal aid providers. This collaborative approach enabled effective prevention and legal assistance, enhancing the capacity of legal aid institutions to support victims of domestic violence.